KARAKTERISTIK DAN KONFLIK TOKOH INVESTIGATOR (ALMUCHAQIQ) DALAM NASKAH DRAMA LUZŪMU MĀ LĀ YALZAMU KARYA TAUFĪQ AL-CHAKĪM (Pendekatan Psikologi Sastra Sigmund Freud) - Hanifah Hikmawati (Arabic Literature Department, 2014)
The discussions in this examination are : (1) How the structure of literature builds the story with prominent character in drama manuscript ‚Luzūmu Mā Lā Yalzamu‛ based on theory of structural Abdul-Bāsith Abdur-Razāq Badr, (2)How characteristic and conflict prominent character in drama manuscript ‚Luzūmu Mā Lā Yalzamu‛ based on the theory of psychoanalysis from SigmundFreud. The Method used in this examination is descriptive qualitative. The purposes of this examination are: (1) Describing the structure which builds the story with prominent character in drama manuscript Luzūmu Mā Lā Yalzamu‛ based on theory of structural „Abdul-Bāsith „Abdur-Razāq Badr, (2)Describing characteristic and conflict prominent character in drama manuscript ‚Luzūmu Mā Lā Yalzamu‛ based on theory of psychoanalysis Sigmund Freud. From the analysis can be concluded some cases, they are : First, the condition and spirit of development cannot separated from external influence, that is psychology influence appeared from positive or negative outside thestrength. In addition it cannot be separated again from internal influence of eachself. Internal influence defined as psychological strength appeared from threesystems of personality, they are id, ego, superego. Second, in drama manuscript Luzūmu Mā Lā Yalzamu‛ part of characteristic and conflict cover prominentcharacter springed by external push. These of mistakes and deviations done byother characters make prominent character, investigator, experienced the conflictand get classification of emotion. These matters make investigator doesmechanism of defense towards the conflicts he faced.